The Rediscovery of a Society Islands Tamau, or Headdress of Human Hair, in the "Cook-Voyage" Forster Collection at the Pitt Rivers Museum - and a Possible Provenance - Coote, Jeremy; Uden, Jeremy (Waka Kuaka, 2013)
In July 2010, a Society Islands tamau, or headdress of human hair, collected on James Cook's second famous Pacific voyage of 1772-74, which had been missing since 1776, was "rediscovered" at the University of Oxford's Pitt Rivers Museum. A report of its rediscovery is followed by a technical description, an account of its conservation, and a partly speculative discussion of its history and provenance.